2014
DOI: 10.5114/fn.2014.45567
|View full text |Cite
|
Sign up to set email alerts
|

Original article The key role of sphingosine kinases in the molecular mechanism of neuronal cell survival and death in an experimental model of Parkinson’s disease

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 55 publications
1
49
0
Order By: Relevance
“…2b,c,d). It has previously been reported that in 1-methyl-4-phenylpyridinium (MPP+) treatment of SH-SY5Y cells, an in vitro PD model, there was a significant decrease in SphK1 gene expression and that Sphk1 inhibition plays an important role in caspase-dependent apoptotic neuronal death35. However, the mRNA levels of S1P signalling molecules such as SphK1, SphK2, S1P 1 and S1P 2 receptors were unchanged under the experimental condition used in the present studies (1 μM α-Syn treatment for 18 hr) although in the proapoptotic conditions such as a higher dose (10 μM) of α-Syn or prolonged time (42 hr) treatment the mRNA level of SphK1 decreased, while that of SphK2 increased (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…2b,c,d). It has previously been reported that in 1-methyl-4-phenylpyridinium (MPP+) treatment of SH-SY5Y cells, an in vitro PD model, there was a significant decrease in SphK1 gene expression and that Sphk1 inhibition plays an important role in caspase-dependent apoptotic neuronal death35. However, the mRNA levels of S1P signalling molecules such as SphK1, SphK2, S1P 1 and S1P 2 receptors were unchanged under the experimental condition used in the present studies (1 μM α-Syn treatment for 18 hr) although in the proapoptotic conditions such as a higher dose (10 μM) of α-Syn or prolonged time (42 hr) treatment the mRNA level of SphK1 decreased, while that of SphK2 increased (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Its pathophysiology involves, e.g., accumulation and spreading of misfolded proteins [48], neuro-inflammation including persistent microglial activity [49], neuro-inflammation including persistent microglial activity [49] and dysfunctions of mitochondrial biogenesis and quality control systems [50]. The latter processes are essentially regulated by bioactive lipids including ceramides, sphingolipids, lysophospholipids, eicosanoids, endocannabinoids, HETEs, omega-3 and omega-6 lipids and EETs [17,[51][52][53][54][55][56][57][58][59]. The relevance of subtle changes in complex regulatory circuits has been taken into account by modern omics-based analysis tools using "gene set enrichment analyses" for the detection of pattern changes [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…The active principal of Nigella sativa seed thymoquinone protected dopaminergic neurons against MPP + -induced cell death in primary mesencephalic cell culture [30]. Inhibition of sphingosine kinase (Sphk1), a regulator of bioactive sphingolipid homeostasis, by SKI II protected the dopaminergic SH-SY5Y cells through an antiapoptotic pathway [29]. However, to date, there is no drug that has provided neuroprotection against dopaminergic cell loss in clinical trials [4].…”
Section: Introductionmentioning
confidence: 99%